A prospective study of psychiatric disorder and cognitive function in systemic lupus erythematosus. Issue 5 (May 1994) - Hay, E M; Huddy, A; Black, D; Mbaya, P; Tomenson, B; Bernstein, R M; Lennox Holt, P J; Creed, F
Abstract : OBJECTIVES–To investigate change in psychiatric disorder and change in cognitive function in patients with systemic lupus erythematosus (SLE) assessed on two occasions two years apart. METHODS–A prospective cohort study of 49 patients with SLE using standardised psychiatric and clinical research methods. RESULTS–The point prevalence of psychiatric disorder (20% and 24%), and of cognitive impairment (23% and 18%), was similar at first and second interview for the whole group. There was, however, considerable change in individual patient's psychiatric status and cognitive function: only 1/9 patients with impairment on two or more cognitive tests at first interview was still impaired at second interview. Change in cognitive function appeared to mirror change in psychiatric status. CONCLUSIONS–These findings suggest that the previously reported high prevalence of cognitive impairment in SLE may be explained by coexisting psychiatric disorder, rather than reflecting subclinical central nervous system (CNS) involvement.